Toward an Epistemic Web - Malcolm D. Hyman; Jürgen Renn (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2012)
In the beginning knowledge was local. With the development of more complex forms of economic organization knowledge began to travel. The Library of Alexandria was the fulfillment - however partial and transitory - of a vision to bring together all the knowledge of the world. But to obtain the knowledge one had to go to Alexandria. Today the World Wide Web promises to make universally accessible the knowledge of a world grown larger. To be sure, much work remains to be done: many documents need to be made available (i.e. digitized if they are not already, and freed from restrictive access controls); and various biases (economic, legal, linguistic, social, technological) need to be overcome. But what do we do with this knowledge? Is it enough to create a digital library of Alexandria, with (perhaps) improved finding aids? We propose that the crucial question is how to structure knowledge on the Web to facilitate the construction of new knowledge, knowledge that will be critical in addressing the challenges of the emerging global society. We begin by asking three questions about the Web and its future. In the remainder of the paper we explore the possibility of an Epistemic Web in the context of a more general discussion of knowledge representation technologies, technologies used for storing, manipulating and spreading knowledge.
Keywords: R10; I31; 330; Wissensgesellschaft; Internet; Erkenntnistheorie